Geographies, Institutions, and Agencies: Ceramic and Socio-Economic Regions and Regionality in (Late) Hellenistic-Late Roman Boeotia, Central Greece (c. 150 BC-AD 700) - Peeters, Dean (Journal of Greek Archaeology, 2021)
It almost goes without saying that explorations of ancient economies developed significantly when one takes the studies by Michael Rostovtzeff and Moses Finley as points of departure. Just as any work, their landmark studies are obviously a product of a certain time. Yet, especially in recent decades, it becomes more and more clear that we can hardly talk about ‘the’ or ‘one’ ancient (type of) economy, since variation and change, rather than homogeneity and stability, characterise the ever-growing archaeological datasets on the basis of which we can try to reconstruct ancient socio-economic systems and practice. Based on the quantity and quality of the currently available archaeological, epigraphic, and historical data, we cannot talk about a unified Mediterranean, Eastern Mediterranean, Aegean, Central Greek, or Boeotian economy.